Biotargets of Cancer in Current Clinical Practice - Bologna, Mauro; SpringerLink (Online service) (Totowa, NJ : Humana Press, 2012)
Biotargets of Cancer in Current Clinical Practice presents an updated and reasoned review of the current status of knowledge concerning the major cancer types with a special focus on the current biomarkers, genes involved and the potential future targets of innovative therapies. The volume includes for each major cancer type, a comprehensive although concise discussion of epidemiology, affirmed and innovative biomarkers for diagnosis, and descriptions of the relevant genes for prognosis and (individualized) therapy through biotarget-specific new molecular treatments, with the latest information on the validation status of each novel biomarker. Individual chapters are dedicated to the major cancer types, plus a special chapter on metastasis. The present debate on patentability of genetic information applied to diagnostics and therapeutics of cancer is also discussed.
Central Nervous System Tumors -- Head and Neck Tumors -- Thyroid Cancer -- Targeted Therapies for Non-Small Cell Lung Cancer -- Non-Hodgkin Lymphomas -- Leukemias -- Breast Cancer -- Esophago-Gastric Cancer -- Colorectal Cancer -- Hepatocellular Carcinoma -- Biomarkers for Prognosis and Molecularly Targeted Therapy in Renal Cell Carcinoma -- Bladder Cancer -- Biomarkers in Prostate cancer -- Ovarian Cancer -- Uterine Cancer: The Influence of Genetics and Environment on Cell Cycling Pathways in Cancer -- Biotargets in Sarcomas: The Past, Present and a Look into the Future -- Melanoma and other skin cancers -- Molecular pathology of cancer metastasis: suggestions for future therapy -- Current and future developments in cancer therapy research: miRNAs as new promising targets or tools.
Keywords: Medicine; Medical laboratories; Oncology; Pathology; Medicine & Public Health; Pathology; Oncology; Laboratory Medicine